The Formation and Development of Zhuhai Shuanglongshan Art District under Post-Industrial Transition - Li, Zimeng; Zou, Yuntao (Urban Planning and Construction, 2025)
Since the 1970s, global deindustrialization has turned urban industrial relics into contested sites of post-industrial transition. Western cities pioneered artist-led regeneration, but districts like New York’s SoHo, London’s Shoreditch, and Berlin’s Kreuzberg typically gentrified within 5–10 years, displacing artists through rising rents and commercialization. In China, state-led urbanization and land-finance logics have accelerated similar outcomes in major art districts such as Beijing’s 798, Shenzhen’s OCT-LOFT, and Shanghai’s M50, reinforcing “gentrification fatalism.” This study examines Zhuhai’s Shuanglongshan Art District as a rare counter-example in a small-to-medium-sized city. Spontaneously formed in 2019 and sustained through 2025, the 73,000 m2 district with over 30 studios has preserved stable low rents, low commercialization, and high artistic originality, with virtually no artist displacement. Using in-depth case study methods—including long-term fieldwork, semi-structured interviews, participant observation, and archival data—this paper reveals how deep university anchoring supplies stable creative talent. Knowledge spillover and symbolic production prioritize academic exploration and cultural dialogue over investment returns, effectively blocking commercial gentrification. Theoretically, it extends Florida’s 3T framework and Bell’s post-industrial theory to micro-level anti-gentrification processes in lower-tier cities, proposing a replicable “university-anchored” model emphasizing low policy embeddedness and organic growth. Practically, it provides a low-cost, sustainable paradigm for China’s over 280 prefectural-level cities, showing that institutional inclusiveness can interrupt the classic gentrification cycle.